“TIME SERIES WORKSHOP” OBSERVATIONS DATA PROCESSING TOOL - Shapovalova, L. L (Одеські астрономічні публікації, 2017)
The new tool for mathematical and visual processing of time series is reresented. The program ”Time Series WorkShop” (TSW) is specialized for processing visual observations of variable stars. An open structure of the allows to apply any old and new mathematical methods for searching any parameters of variability. The program also allows to visualize the time series and any calculation results (periodograms, histograms, light curves and their smoothing curves) in a camera-ready form. The following mathematical methods are realized: the periodogram analysis with “prewhitening”. the method of ”running parabolae”, some methods of correction of observational series, including that taking into account the differences of the instrumental systems of individual observers. The possibility of exporting images into standard graphic formats and printing is specified. The program Time Series WorkShop has passed test trials at processing of visual observations of semiregular variable stars on the AFOEV and VSOLJ databases. TSW. like any other program product, will be developed by adding new mathematical methods and visualization improvement.